THE QUALITY OF ISLAMIC EDUCATION LEARNING ASSESSMENT: AN EVALUATIVE STUDY AT THE ELEMENTARY, JUNIOR HIGH, AND HIGHER EDUCATION LEVELS - Ahwil Lutan Hidayah; Sofwatun Nida; Arif Zefrizen (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
A quality assessment instrument is an important component in the learning evaluation process to measure the achievement of student learning outcomes. This article aims to describe how to analyze the quality of Islamic Religious Education (PAI) learning assessment instruments at the primary, secondary, and tertiary education levels. The method used is a literature study with a descriptive-analytic approach to the aspects of validity, reliability, difficulty level, differentiating power, and effectiveness of distractors in assessment instruments. The results of the analysis show that the quality of assessment instruments is often not optimal. At the primary level, aspects of suitability with learning indicators and materials are the main focus. At the intermediate level, the distribution of question difficulty levels is not balanced, with the dominance of questions that are too easy. At the high level, there is a need to clarify the substance of the material and avoid redundancy of questions. An ideal assessment instrument must meet the principles of validity, reliability and fairness and be prepared according to learning needs. This article emphasizes the importance of systematic development and analysis of assessment instruments to ensure the quality of accurate and representative learning evaluation results. Thus, efforts are needed to improve educators' competence in developing and analyzing assessment instruments according to educational evaluation standards.